Limitasi Keluar Rumah Bagi Perempuan ‘Iddah Wafat dalam Perspektif Maslahah Mursalah - Baharun, Hasan; Adhimiy, Syafiqiyah (Universitas Islam Negeri Raden Intan Lampung, 2018)
Although there is no shârih (clear) propotion about the prohibition on going out of the house for a woman who has just been left dead by her husband (‘iddah wafat), but jurists of the four Islamic schools have agreed that women who are iddah wafat may not leave the house except in emergencies or in hajiyah (desperate need). But then they differed about the time and limit of the ban. This study examines the prohibition on going out of the house for a woman who has just been left dead by her husband according to the ulema of ‘four schools. This study uses descriptive analysis method, with analytical techniques in the form of inductive, deductive and comparative. Based on the results of the study, it can be concluded that women in ‘iddah wafat are allowed to leave the house if there is a need that requires them to leave the house in the morning in hajiyah (needs). While for the night, she may leave the house only at times and in dharâriyah (emergency). Limitation to leave the house for women ‘iddah wafat in hajiyah or dharûriyah conditions is solely for benefit and does not contradict to the principles of maslahah mursalah.Although there is no shârih (clear) propotion about the prohibitionon going out of the house for a woman who has just been left dead by her husband (‘iddahwafat), but jurists of the four Islamic schools have agreed that women who are iddah wafatmay not leave the house except in emergencies or in hajiyah (desperate need). But thenthey differed about the time and limit of the ban. This study examines the prohibition ongoing out of the house for a woman who has just been left dead by her husband accordingto the ulema of ‘four schools. This study uses descriptive analysis method, with analyticaltechniques in the form of inductive, deductive and comparative. Based on the results ofthe study, it can be concluded that women in ‘iddah wafat are allowed to leave the houseif there is a need that requires them to leave the house in the morning in hajiyah (needs).While for the night, she may leave the house only at times and in dharâriyah (emergency).Limitation to leave the house for women ‘iddah wafat in hajiyah or dharûriyah conditionsis solely for benefit and does not contradict to the principles of maslahah mursalah.